Design Principles for a Higher Education Course Focusing on Lifelong Learning - Brodén, Karin; Johansson, John; Bergkvist, Linda; Humble, Niklas; Mozelius, Peter (Electronic journal of e-Learning, 2024)
Lifelong learning for solving work assignments is essential for societal and personal development. Higher education is one natural part of lifelong learning and, therefore, needs to be re-focused from solely younger students to include professionals and their development goals. One problem related to giving a course for professionals is their struggle between work assignments and the course. Focusing on the added perspective of professionals for higher education, this study presents five design principles for courses for professionals. Design principles are guidelines based on experience and iterative development in higher education. The empirical data comes from a course in digitalisation and digital transformation, which was given thrice. The course participants were professionals from private and public organisations in Sweden. The empirical data originates from the professionals who made a check-in, mid-term evaluation, and evaluation after the course, resulting in 75 entries. Two researchers analysed the first two course entries inductively, forming the foundation for the first round of design principles. The course design for the third round was then revised according to its weaknesses. Based on the strengths and weaknesses found in empirical material from all three courses, the current design principles are professional pathways referring to new knowledge directly linked to real-world applications, knowledge evolution, meaning gradual integration of knowledge using seminars and examination assignments, preparedness protocol focusing on updated information and structured templates for the seminars. Further, the design principle of collaborative connection includes discussion where professionals exchange experiences, and the last principle, learning fusion, directs toward blended learning by combining face-to-face seminars and films. The revised course design, according to the design principles, implied that the number of professionals graduating and their grades increased. The findings of this study add theoretically to existing knowledge and practical implications by providing design principles that higher education teachers and other stakeholders can use to design or revise professional development courses. The design principles could be used stand-alone or combined to increase professionals' learning and satisfaction.